The Effectiveness of The Use of Leaflet Media on The Prevention Behavior of Pathological Women of Childbearing Age in Polindes, Kedaton Village, Kapas District, Bojonegoro District - Eri Puji Kumalasari (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Background: Flour albus causes discomfort so that it requires increased behavior in preventing fluorine albus. The behavior of preventing vaginal discharge in fertile age women is still a health problem that needs attention. The Health Promotion Model theory emphasizes the active role of fertile age women in regulating healthy living behavior which aims as the prevention of a disease including fluorine albus or vaginal discharge, one of which is health education through leaflet media (Rachmadianti, 2019). Purpose: to determine the effectiveness of the use of leaflet media on the prevention behavior of pathological leucorrhoea in fertile aged women at the Polindes, Kedaton Village, Kapas District, Bojonegoro Regency. Methods: The research design used in this study was a pre-experimental design with one group pretest-posttest design. The sample in this study were some of the women of fertile age at the Polindes Village of Kedaton, Kapas District, Bojonegoro Regency as many as 39. The data analysis technique used in this study was the Mc Nemar test statistic. Results: more than some respondents had positive behavior, namely as many as 20 (51.3%) before being given leaflet media, and more than some respondents had positive behavior, namely as many as 31 (79.5%) after being given leaflet media. The results of calculations by SPSS with the Mc Nemar test showed that the significance value obtained to analyze the effectiveness of leaflet media on pathological vaginal discharge prevention behavior in women of childbearing age was 0.003. With a significance level of 5%, 0.003 <0.05, so H1 was accepted and it was concluded that the use of leaflet media was effective in preventing pathological vaginal discharge behavior in women of childbearing age. Conclusion: In women (women of childbearing age) are expected to always practice ways to prevent pathological vaginal discharge in everyday life.